Respuesta :
Answer:
Option D, -2/6
Step-by-step explanation:
Slope Formula: [tex]\frac{y2-y1}{x2-x1}[/tex]
Step 1: Determine x1, x2, y1, y2
(x1, y1) is (4, -3)
(x2, y2) is (-2, -1)
Step 2: Plug in
m = [tex]\frac{-1 - (-3)}{-2 - 4}[/tex]
m = [tex]\frac{-1 + 3}{-6}[/tex]
m = [tex]-\frac{2}{6}[/tex]
Answer: Option D, -2/6
Answer:
- 2/6
Step-by-step explanation:
Slope = y2 - y1 /x2 - x1
Given
x1 = 4
y1 = -3
x2 = -2
y2 = -1
Slope = -1 -(-3) / -2 -4
Negative negative becomes positive
= -1 + 3 /-2 - 4
= 2/-6
= - 2/6